Análise qualitativa da formação dos discentes que fizeram parte das empresas júniores de engenharia civil - Lima, Bruno Chaves (Universidade Federal Rural do Semi-Árido, 2021)
The Junior Enterprise Movement (MEJ) appeared in France in 1967 and arrived in Brazil in the eighties. Junior companies seek to provide their members with opportunities to experience the job market in terms of professional training for the exercise of their profession, thus improving the process of training their professionals. During the entrepreneurial experience, skills, technical skills in engineering and entrepreneurship (as established by the Ministry of Education and the World Economic Forum) are developed in junior entrepreneurs. This study sought to identify the perceptions that business experience causes in the training of members of companies in the civil engineering course at the Universidade Federal Rural do Semi-Árido. The survey was carried out through a virtual questionnaire using the Google Forms tool. According to the respondents' perceptions, the most developed technical skills were those aimed at working in multidisciplinary teams, project coordination and engineering services. The most developed skill of the future was related to leadership. It was noted that the development of these activities provides a better introduction to the job market and professional career
Keywords: Engenharia civil; Movimento Empresa Junior; Competências; Projetos multidisciplinares; Liderança; Civil engineering; Junior Enterprise Movement; Skills; Multidisciplinary projects; Leadership; ENGENHARIAS::ENGENHARIA CIVIL